Unique CoS hierarchitectures for high-performance lithium ion batteries. Issue 42 (10th October 2018) - Lin, Weijuan; Huang, Yingheng; He, Guoqiang
Abstract : Lantern-like CoS hierarchitectures, having a perfect crystal structure, a high specific surface area and lots of nanoscale 3D channels, are synthesized. Abstract : Nanostructured lantern-like CoS hierarchitectures were fabricated in situ growth via a facile one-pot hydrothermal process from bottom to top, using only deionized water as a green growth solvent without any templates or surfactants. Based on time-dependent experiments, a possible growth mechanism for the lantern-like CoS hierarchitectures was proposed, which has a positive effect on the design of desirable micro-/nanostructures. At a current density of 100 mA g −1, the initial discharge specific capacity of the lantern-like CoS hierarchitectures is 1276 mAh g −1, higher than that of CoS flower balls (1127 mAh g −1 ), and they also show stable cycling, with a capacity of about 352 mAh g −1 at a current density of 1 A g −1 over 1000 cycles. This suggests that the CoS hierarchitectures display better electrochemical properties and have potential applications in high-capability lithium-ion batteries.